Evaluation of the possible association between acantholysis and anti‐desmogleins 1 and 3 values in pemphigus vulgaris and pemphigus foliaceus - Maryam Mobarakabadi (Journal of Cutaneous Immunology and Allergy, 2019)
Abstract Objectives Acantholysis is the main pathologic finding in pemphigus, and its location has been historically used to distinguish the major subtypes of pemphigus vulgaris (PV) and pemphigus foliaceus (PF). While suprabasal clefts are present in PV, PF includes intragranular or subcorneal clefts. After the introduction of anti‐desmoglein ELISA, PF is characterized by anti‐Dsg 1 and PV by anti‐Dsg 3 autoantibodies. However, pathological and serological findings are not consistent in all patients. In this study, we tried to investigate the agreement between serological and pathological findings for the diagnosis of pemphigus. Methods We restudied the acantholysis location in skin biopsy samples of 168 pemphigus patients and compared the subtypes of pemphigus based on anti‐Dsg1/3 ELISA and acantholysis locations. Results In 33 (19.6%), 100 (59.5%), and 35 (20.8%) of patients, acantholysis was observed in the upper half, the lower half, and throughout the epidermis, respectively. The mean anti‐Dsg1 and anti‐Dsg3 values were 169.76 and 43.45 U/mL in upper clefts and 120.53 and 157.88 U/mL in lower clefts, respectively. By assuming anti‐Dsg1/3 as the gold standard of diagnosis of pemphigus, the sensitivity and specificity of cleft location‐based diagnosis were calculated as 90.2% and 80% for PV and 80% and 90.2% for PF, respectively. There was an overall agreement of 87.97% between histological and serological diagnosis. Conclusions The histological findings in PV and PF are not necessarily correlated with sera antibodies' profile. Clinical manifestations, histopathological findings, direct immunofluorescence, and serologic study are all required to accurate diagnosis of the pemphigus and differentiate its subtypes.